State intelligence and the politics of Zimbabwe's presidential succession - Tendi, B (Oxford University Press, 2016)
Since the late 1990s Zimbabwean politics has been shaped by the political succession war raging within the ruling ZANU PF party. The internal fight to succeed President Robert Mugabe pitted a faction controlled by retired General Solomon Mujuru, who was fronting his wife Joice Mujuru, against another faction led by Emmerson Mnangagwa, a government minister. The competition between these factions reached a crucial stage in 2014, when Mugabe dismissed Joice Mujuru as Vice-President and purged her key allies in ZANU PF and the government. This article examines the role of state intelligence in this struggle, arguing that the Military Intelligence (MI) leadership, which supported Mnangagwa in the succession conflict, placed Joice Mujuru under surveillance and constructed a controversial gendered case to destroy her bid to succeed Mugabe. In contrast, some elements in the principal civilian intelligence institution, the Central Intelligence Organization, conducted a surveillance operation against the Mnangagwa faction in order to support Joice Mujuru's power bid. The article widens scholarship on the security sector's political interventions in Zimbabwean politics, while emphasizing how the gendered dimensions of surveillance can reinforce patriarchal national politics.